Les géographes et la pensée coloniale française : l’Indochine à travers les thèses de Charles Robequain et Pierre Gourou - Dany Bréelle (Unité Mixte de Recherche 8504 Géographie-cités, 2009)
The very first doctorate theses in French regional geography in regard to Far East regions, The Thanh Hoá Geographical Study of an Annamite Province from Charles Robequain, and The Peasants of the Tonkin Delta from Pierre Gourou, were published respectively in 1929 and 1936. This article deconstructs the interpretation and the rhetoric of the two discourses which are underlying the two works. It compares these with other representative discourses of the 1920s and 1930s, and questions the relevance and approach of each of the two authors. It highlights the way two geographers belonging to the French Empire, with a similar university background and both working in the Indochinese field, have constructed two dissimilar geographical discourses, while contributing their expertise in the constitution of a French as well as Vietnamese corpus of knowledge that describes the peasant structures and dynamics.